Enfleurage Essential Oil From Jasmine and Rose Using Cold Fat Adsorbent - Siswati Soe’eib; Nyoman Puspa Asri; A. S Dwi Saptati N. H.; Diah Agustina P (Fakultas Teknik, Universitas Katolik Widya Mandala Surabaya, 2016)
Flower essential oils can’t be taken by distillation, which is the oils’ component will damage because of hydrolysis and polymerization process. High-boiling components can’t be transported by water vapor so its yield and quality of the oil product is low. The alternative method for producing flower essential oils is an enfleurage process. Enfleurage is essential oil extraction process using cold fat, where the scent of flowers is absorbed by fat. The aim of the research is to obtain information about the optimum conditions based on essential oils of flowers through enfleurage method. Enfleurage process was begun with prepared the adsorbent which was made from mixing of vegetable fat and animal fat in ratio of 1:1. Fat was heated up to 60 0C further stirring for 15 minutes. As long as stirring, the fat mixture was mixed with benzoate and stirred for 2 hours. After the adsorbent was ready, a chassis was smeared with a layer of fat and flowers were palced in surface of fat for 1, 3, 5, 7, 9 and 11 days. The process was repeated with change the flowers every 24 hour with fresh flowers. When contact time had finished, fat was extracted using alcohol and it was separated by vacum distillation. The maximum yield was obtained for 5 days 0.89 % for jasmine, 0.88 % for rose and 0.84 % for frangipani. The enfleurage process is an effective method to produce flowers essential oils. The success of it depends on type of adsorbent, the level of florescence, as well as enfleurage’s period.